Linear and spatial variability of eucalyptus dendrometric attributes correlated with the properties of a Typic Haplustox soil (Oxisol) in the Brazilian savannah - da Silva Martins, Iris Mariane [UNESP]; Silva, Tatiane Carla [UNESP]; Troleis, Maria Julia Betiolo [UNESP]; de Souza, Paulino Taveira [UNESP]; Sena, Karla Nascimento [UNESP]; Montanari, Rafael [UNESP] (Universidade Estadual de Londrina, 2022)
Effects of soil attributes using the geostatistical tool improves the interpretation of specific soil management. Thus, this study aimed to evaluate the physical, chemical, and microbiological properties of a Typical Haplustox (Oxisol), identifying those with the best linear and spatial correlation with eucalyptus (Eucalyptus spp.) vegetative growth. The experiment was conducted at the Teaching, Research, and Extension Farm (FEPE) of the Universidade Estadual Paulista (UNESP), Campus of Ilha Solteira. Thirty-five points spaced 13 meters apart were demarcated for analysis, which were distributed in 5 rows of 7 points each. From each point, 2 soil samples were collected from the 0-10 cm depth layer. The physical, chemical, and microbiological soil properties evaluated were: sand, silt, and clay contents; penetration resistance (PR), gravimetric moisture (GM), real density (RD), microbial biomass carbon (MBC), respirometry (CO2-C), metabolic quotient (qCO2), organic matter content (OM), and hydrogenionic potential (pH). The eucalyptus attributes assessed were: plant height (PH) and circumference at breast height (CBH). Each attribute was analyzed by descriptive statistics using the SAS software. Data frequency distribution was verified by the Shapiro Wilk method, and geospatial changes were analyzed by the GS+ software. The soil property that best explained the variability in eucalyptus dendrometric attributes was real density (RD). Except for RD, all properties did not show spatial dependence (i.e., pure nugget effect), which significantly represents eucalyptus vegetative performance.
Variabilidade linear e espacial dos atributos dendométricos do eucalipto correlacionados com atributos de um latossolo no cerrado brasileiro
Keywords: Eucalyptus grandis; Geostatistics; Site-specific zone management; Soil management; Soil microbiology